Enhancing CO2 mass transfer in algal raceway ponds through wave generation - Van Der Linde, Frans Johannes (Department of Chemical Engineering, 2025)
Microalgae possess great potential to mitigate the growing energy, environmental and food-related challenges of our time. The large scale cultivation of microalgae is currently mostly done using raceway ponds. These ponds however suffer from low algal productivities compared to closed photobioreactors, in part due to inadequate CO2 mass transfer into the culture. A previous study at the University of Cape Town explored a method to improve the transfer of atmospheric CO2 into the pond through surface turbulence created by inserting a sloping structure into the pond. This showed promise as a less energy and resource intensive alternative to CO2 gas sparging. Depending on the design, the slope can either act like a beach, to mimic the formation of shoaling ocean waves, or act like a weir to create a hydraulic jump. This study aimed to shed light on the effect of different slope parameters on the CO2 mass transfer rate, hydrodynamics and energy demand of a lab scale raceway pond, and through this improve on the previous slope designs. For the weir-like slope designs, a 24-1 fractional factorial design of experiments (DOE) was performed to evaluate the effects of the different slope parameters. The DOE considered the upslope angle (25 ° and 54 °), downslope angle (10 ° and 39 °), slope height (9 cm and 10 cm) and paddlewheel rpm (19.8 and 28.9). The measured responses included the fluid hydrodynamics, CO2 mass transfer rate and energy demand. These responses were also measured for a slope that was designed to create waves similar to shoaling ocean waves. This design had set parameters, selected based on theoretical calculations. The new slope designs were compared to a control without a slope, as well as the previous best performing slope designs. Based on the results of the DOE, three slope configurations were selected and compared to a control in terms of the algal productivity, where Scenedesmus sp. was cultivated. To potentially further decrease the energy demand of the raceway, a propeller system was investigated as an alternative to the paddlewheel, since a propeller is thought to be a more energy efficient fluid driving device. The experiments were performed in an indoor lab scale raceway pond with a 62 L working volume operated at a fluid depth of 12 cm, with no gas sparging. The hydrodynamics were quantified through conductivity tracer experiments and photographic imagery. The CO2 mass transfer rate was measured using a pH method, which monitored the decrease in the fluid pH as CO2 transferred into the pond. The CO2 mass transfer coefficient, kLa, was primarily used to assess the gas mass transfer rate. To quantify the energy demand, theoretical calculations were performed and the actual energy input was measured using a power meter. With the slope designed to imitate ocean waves it was not possible to create breaking waves, likely due to the dominating effects of surface tension on this small scale. As a result, the kLa was not improved compared to the control. However, the mixing time was decreased by 18 % while the fluid velocity was not altered. The weir-like slopes on the other hand led to an increase in kLa compared to the control due to adequate surface turbulence from the hydraulic jump. The factorial DOE however revealed that this increase was independent on the different slope parameters (in the range of values tested). This meant that variation in the slope parameters could not further improve on the kLa compared to the previous slope designs. The average increase in kLa compared to the control ran at the same rpm was 12 ± 2 % at 19.8 rpm and 16 ± 5 % at 28.9 rpm. In this case, the choice in selecting the ideal slope parameters should therefore be based on the resulting hydrodynamics and energy demand. Compared to the previous slope designs, when using the same rpm, it was possible to increase the fluid velocity from 6.4 ± 0.1 cm s-1 to 10.0 ± 0.3 cm s-1 and decrease the mixing from 142 ± 1 s to 112 ± 0 s. This was primarily due to a lower slope height, indicating that it is the most important slope parameter to optimize. The weir-like slopes however led to a considerable increase in the energy demand of the system, which was incorporated in the algal productivity for comparative purposes. The slopes led to an increase in algal productivity of up to 10 % at the same rpm as the control. This increase in algal productivity due to the slope was closely related to the increase in kLa, which suggested that the culture was CO2 limited. The control however had the highest productivity per unit of theoretical energy requirement (0.67 ± 0.02 g L-1 day-1 W-1 compared to the highest of 0.42 g L-1 day-1 W-1 achieved with a slope). These results suggested that on this scale a slope might not be required, as a similar effect could be achieved by simply increasing the paddlewheel rpm. The energy demand of the raceway could further be reduced by using a propeller, which showed a reduction of 56 % in the actual energy input compared to the paddlewheel. The propeller was however not as good of a gas mass transfer device. The kLa measured with the propeller system was 28 % lower compared to the paddlewheel, but the kLa per unit of actual energy input was 58 % higher. The motor for the paddlewheel was however oversized, which contributed to a higher actual energy input for the paddlewheel system. On a larger scale, however, the overall mixing and gas mass transfer in raceway ponds are less dominated by the paddlewheel, meaning that the effects of the propeller, as well as the slopes, could be more significant when scaled up. These results have shown the need to evaluate the slopes on a larger scale, where additional factors come into play. With the slope that imitates a beach, it could be possible to successfully create breaking waves due to a less dominating effect of surface tension. These slopes can then potentially improve the gas mass transfer without a significant negative effect on the fluid velocity and energy demand. It was also shown that the slopes greatly improved the mixing in the pond, which would play a more important role on a larger scale with the presence of temperature gradients and varying light. The results of this study could be used to guide the design of the slopes for a larger scale. The large-scale designs should be compared to a gas sparging system on the same scale, to adequately show that the slopes are a more cost and resource effective alternative to gas sparging.